2020
DOI: 10.1016/j.jjcc.2019.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical findings of gadolinium-enhanced cardiac magnetic resonance in Fabry patients

Abstract: Recently, we reported that nearly one-third of males and onefourth of females had LVH among Fabry patients prior to enzyme replacement therapy (ERT) [9]. We also showed that the appearance of LVH was age-dependent, and the progression rate of left ventricular mass (LVM) was higher in male patients than in female patients [9,10]. LVH itself is a key manifestation of a heart A B S T R A C T Background: Fabry disease is one of the causes of left ventricular hypertrophy (LVH) and can be treated with enzyme replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…Accordingly, myocardial native T1 values progressively decrease as LV wall thickness increases. Advanced hypertrophic stages of cardiac AFD are characterized by myocardial inflammation and development of interstitial fibrosis, with pseudo-normalization of native T1 times and extensive myocardial LGE, characterized by a typical pattern of distribution allowing a potential differential diagnosis from other forms of hypertrophic cardiomyopathy [ 30 , 40 , 41 ]. Native T1 mapping represents an important biomarker, as it allows early detection of cardiac damage in a pre-hypertrophic stage and discrimination between control subjects and AFD patients without LVH.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, myocardial native T1 values progressively decrease as LV wall thickness increases. Advanced hypertrophic stages of cardiac AFD are characterized by myocardial inflammation and development of interstitial fibrosis, with pseudo-normalization of native T1 times and extensive myocardial LGE, characterized by a typical pattern of distribution allowing a potential differential diagnosis from other forms of hypertrophic cardiomyopathy [ 30 , 40 , 41 ]. Native T1 mapping represents an important biomarker, as it allows early detection of cardiac damage in a pre-hypertrophic stage and discrimination between control subjects and AFD patients without LVH.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial tissue is characterized mainly by the method of late gadolinium enhancement (LGE) following intravenous administration of gadolinium and typically presents midmyocardial fibrosis in the basal and midventricular inferior-lateral wall of the left ventricle [9,[12][13][14]. However, atypical patterns of late enhancement in the basal anteroseptal and apical segment have also been observed in patients with asymmetric hypertrophy of the interventricular septum or with apical hypertrophy respectively [10,11].…”
Section: Main Body 1) Storage Diseases Fabry Diseasementioning
confidence: 99%
“…In FD LGE is usually located in the inferolateral basal wall of LV, with a mid-wall distribution (10). However, this pattern of LGE is not specific of Fabry disease, being found in other conditions as myocarditis, arrhythmogenic cardiomyopathy, sarcoidosis etc (45) In table 2 are shown data of LGE presentation reported in FD studies (10,23,24,26,(46)(47)(48)(49)(50)(51)(52). The overall prevalence of LGE in FD was 33% (in 145 out of 442 patients).…”
Section: Late Gadolinium Enhancement and Extracellular Volume Mapping...mentioning
confidence: 99%
“…The overall prevalence of LGE in FD was 33% (in 145 out of 442 patients). Eight studies also reported the distribution of LGE in LV myocardium (10,24,(46)(47)(48)(49)(50)(51). LGE was non-ischemic in all the cases, 113 patients (94%) presented inferolateral basal midwall LGE, and 7 (6%) a different pattern.…”
Section: Late Gadolinium Enhancement and Extracellular Volume Mapping...mentioning
confidence: 99%